A NOVEL APPROACH FOR CONFIGURING THE STIMULATOR OF A BCI FRAMEWORK USING XML - Indar Sugiarto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
In a working BCI framework, all aspects must be considered as an integral part that contributes to the successful operation of a BCI system. This also includes the development of robust but flexible stimulator, especially the one that closely related to the feedback of a BCI system. This paper describes a novel approach in providing flexible visual stimulator using XML which has been applied for a BCI (brain-computer interface) framework. Using XML file format for configuring the visual stimulator of a BCI system, we can develop BCI applications which can accommodate many experiment strategies in BCI research. The BCI framework and its configuration platform is developed using C++ programming language which incorporate Qt’s most powerful XML parser named QXmlStream. The implementation and experiment shows that the XML configuration file can be well executed within the proposed BCI framework. Beside its capability in presenting flexible flickering frequencies and text formatting for SSVEP-based BCI, the configuration platform also provides 3 shapes, 16 colors, and 5 distinct feedback bars. It is not necessary to increase the number of shapes nor colors since those parameters are less important for the BCI stimulator. The proposed method can then be extended to enhance the usability of currently existed BCI framework such as BF++ Toys and BCI 2000.